Foodstagramming hyperreality in consumption behavior in Indonesia - Nabilah Mahdiyyah Destriana; Nurhadi Nurhadi; Sigit Pranawa (Program Pascasarjana Universitas Negeri Yogyakarta, 2020)
This research studies the foodstagramming phenomena that happened on most young people in Surakarta which has been the new lifestyle that causes hyperreality in social media. The purpose of this study was to know the motives behind the activities of foodstagramming done by Instagram users and their effects on the people’s consumptive interest that impacted the hyperreality phenomenon on social media. The actions of foodstagramming are now widely popular since more cafés and restaurants are built-in Surakarta. Technology advancement has changed the eating culture, which in the past, it sees as a necessity fulfillment. Still, now it becomes the ‘mark’ of what to expose to the public through simulation in social media that eventually forms fake realities, as mentioned by Jean Baudrillard as hyperreality. This study used the qualitative approach and phenomenology method to dig out the motives behind the Surakarta people’s activities foodstagramming. The data collection techniques used were interviews, observation, and documentation from Instagram, news websites, and survey results about consumptive patterns and social media usage. The informant’s criteria were Instagram users, such as cafés and restaurant consumers, entrepreneurs, and the café or restaurant workers. The data analysis technique was an interactive model data analysis by Miles and Huberman. The result showed that ‘Makan Cantik’ and Foodstagramming were simulations that intentionally create to form a particular image to represent the social status and gain prestige. ‘Makan Cantik’ and Foodstagramming were called hyperreality in social media where fake realities were exposed to be more real than the truth itself.